History of Islamic Trading Civilization in the Pre-Prophetic Period (570-610 M) - Ibnu Hajar; Wachida Muhlis; Khairul Mizan; Zulfi Mubaraq (Journal of Islamic Civilization, 2023)
The history of Islamic Trading Civilization during the Pre-Prophecy period (570-610 M) is critical to study. The condition of the pre-prophetic Arab people had progress in the economic field, especially in agriculture and trade. In the progress of Arab tradeat that time, due to advanced agriculture, this progress was marked by the export and import activities they carried out. This paper aims to understand three things: first, the concrete form of trade; Second, the factors that affect trade. These three implications affect trade. The method used is library research. The literature study uses articles as the primary data source and journals selected according to the title’s relevance. The most important findings in research on the history of Islamic civilization in the Pre-Prophetic Period include three. First, trading in Islam during the pre-prophetic period can provide best practices through the example of the Prophet Muhammad. Second, internal factors, the principles of siddiq (honest attitude), amanah (trustworthy), fathanah (intelligent) and tabligh (argumentative and communicative) were applied in trading during the pre-prophetic period. External factors intertwined tribes into politics with local and regional trade agreements between the rulers of the Hijaz on the one hand and the rulers of Sham, Persia and Ethiopia on the other. Third, the economic condition of the Arab nation which is growing rapidly due to its strategic geographical location, especially the Yemen and Hijaz areas